Mpox: Epidemiological, immunopathogenic aspects and pre- and post-infection management - Yago Soares Fonseca; Calila Oliveira Alves; Gabriela Garcia de Carvalho Laguna; Beatriz Rihs Matos Tavares; Lohana Guimarães Souza; Grasiely Faccin Borges; Luiz Henrique Santos Guimarães (Hospital de Clínicas de Itajubá, 2023)
Mpox or Variola M is a zoonosis caused by viruses of the genus Orthopoxvirus, which also cause common smallpox. It is a disease considered rare and self-limiting, being endemic in African countries. However, in 2022, it gained prominence due to the global outbreak that began when the world was still recovering from the COVID-19 pandemic. Thus, as it is an emerging disease, this review aims to point out general aspects of what is known so far about Mpox, from its immunopathogenesis to current forms of prevention and post-infection care.